Aspectos do controle biológico de Botrytis cinerea Pers. Ex. Fr. em videira - Hamann, Fábio André (2011)
Rio Grande do Sul (RS), the most important state of grape production in Brazil, harvests, approximately, 780 thousand tons annually. One of the biggest constraint factors to the obtainment of higher production numbers is the incidence of late season diseases in vineyards, being botrytis bunch rot, caused by Botrytis cinerea, one of the major contributors for field and post-harvest losses. Red grapes can show more resistance against this fungus, due to higher levels of phenolic compounds. The use of biological control agents (BCAs) emerges as a promising alternative to control botrytis disease. For this reason, the objectives of this study were to test isolates from this fungal pathogen, originated from the two main grape production regions in the state of RS, trough in vitro direct confront test against BCAs fungal isolates (Trichoderma spp. and Gliocladium sp.) and to test the same pathogen isolates on semi in vivo biological control, against the BCAs isolates which obtained the highest biological activity during the in vitro test, on the post-harvest storage of table grapes, on a red and a white cultivar. The B. cinerea isolates used were UFSM SG01, UFSM SG02, from serra (mountain range) region, UFSM CM01, and UFSM CM02, from campanha meridional (meridional pampas) region. The BCAs isolates used in this study were Tricoderma spp., UFSM T20, UFSM T17, UFSM T15.1 (obtained from soil), UFSM TSG, UFSM TCM (obtained from the same grape bunches where B. cinerea was isolated, representing each region), and Gliocladium sp., UFSM G4DB (obtained from soil). UFSM TSG, UFSM TCM and UFSM T15.1 showed the highest biocontrol activity (B. A.) in vitro, in general over 50% against all B. cinerea isolates. The same BCAs were selected to be used at the semi in vivo test with detached berries for three inoculation periods: B+T, pathogen and BCA inoculated at the same time; B+24hT, pathogen inoculated first and BCA 24 h later, T+24hB, BCA inoculated first and pathogen 24 h later. A higher control, considered as the lower damage level, on T+24hB period, showed the importance of preventive treatment. Cracks on berries played a more important role than the color of the skin for botrytis infection.